Entropy generation and accumulation in biological systems. (20th November 2020) - Yildiz, Cennet; Semerciöz, Ayşe Selcen; Yalçınkaya, Bahar Hazal; Ipek, Tanya Deniz; Ozturk-Isik, Esin; Özilgen, Mustafa
In living systems, entropy is generated as the result of the metabolic activity, most of it is exported, while only a small fraction is accumulated. Accumulation reveals itself as structural impairment, regarded as a sign of aging and measured in terms of information entropy. This study shows that higher blood flow rate fuels higher work performance and cause higher entropy generation. Since a very important fraction of the work performance in a living system is the internal work, including those of the heart beating, breathing, formation of new molecules, maintenance of the body, muscle contraction-relaxation process, signal transmission in neurons and active transport of some molecules, entropy generation should not be regarded detrimental to the organisms as long as entropy is not collected, but exported. Anterior cingulate cortex, a constituent of the grey matter in the brain, is the neuroanatomical interface between emotion and cognition. In the literature, lower blood flow, is reported as the cause of the shrinking grey matter volume, i.e., entropy accumulation, with aging, confirming that entropy generation within an organ is not detrimental for health, as long as the entropy does not accumulate but flushed out.